Detecção molecular de Ehrlichia canis em cães do Pantanal do estado de Mato Grosso, Brasil - Santos, Luana Gabriela Ferreira dos (2012)
The present study aimed to evaluate the presence of Ehrlichia spp. in dogs from Poconé, Pantanal of Mato Grosso and determine molecular prevalence through Polymerase Chain Reaction in two stages (nestedPCR), associating risk factors for infection. A total of 320 dogs from urban and rural areas were evaluated. Sixty (18.75%) dogs were positive, 25 (15.62%) from urban area and 35 (21.87%) from rural areas (P> 0.05). There were no variables associated with positivity. Eighteen samples from urban and 15 from rural area were sequenced. In urban areas, 15 samples and 13 in rural areas were 100% identical to E. canis sequences deposited in Genbank. Five samples showed lower values of similarity (99-98%) The results were compared with a previous serological study with the same dog population in this region. This study reports the first molecular detection of Ehrlichia species in dogs from North Pantanal.